Pengaruh Suasana Toko, Keragaman Produk dan Promosi Terhadap Keputusan Pembelian ( Studi Pada Konsumen Ramayana Department Store Kota Malang) - Iva Nurdiana Nurfarida; Dianawati Suryaningtyas; I’if Pravita Sari (Jurnal Riset Mahasiswa Manajemen, 2018)
The purpose of this study was to determine the effect of the store atmosphere, product diversity, and promotion of purchasing decisions on Ramayana Department Store consumers in Malang. The independent variables in this study are Store Atmosphere, Product Diversity and Promotion, then the dependent variable is the Purchasing Decision. This research was conducted at the Ramayana Department Store Malang, the sample in this study were 112 respondents. The sampling technique in this study uses accidental sampling. The analysis technique used in this study is Multiple Linear Regression. Based on research that has been done the results show that the Store Atmosphere, Product Diversity and Promotion have a partial and simultaneous effect on Purchasing Decisions.